PENGARUH MOTIVASI KERJA TERHADAP KINERJA PERANGKAT DESA KAIDUNDU KECAMATAN BULAWA KABUPATEN BONE BOLANGO - Mamonto, Rahmadayanti; Ismet Sulila; Yacob Noho Nani (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
The Effect of Work Motivation on the Performance of Kaidundu Village Apparatus, Bulawa District, Bone Bolango Regency. S1 Public Administration Study Program, Department of Public Administration, Faculty of Social Sciences, Gorontalo State University. Supervisor I Ismet Sulila, , and Supervisor II Yacob Noho Nani, This study aims to determine the Influence of Work Motivation on the Performance of Kaidundu Village Apparatus, Bulawa District, Bone Bolango Regency. The sample in this study is 12 people consisting of 12 employees. The research method used is quantitative. The type of data in this study is primary. The data collection technique is by distributing questionnaires. The data analysis technique uses simple linear regression. The results of the analysis showed that the t-count for the work motivation variable was 2.659. Meanwhile, the t-table value of the significant level is 5% and the free degree n-k or 12-2=10 is 2.228. If the two t-values are compared, then the t-calculated value is greater than the t-table (2.659>2.228). Thus, the hypothesis that there is an influence of work motivation on the performance of village apparatus is accepted. Therefore, it can be concluded that at the level of 95% that work motivation has a positive and significant effect on the performance of the Kaidundu Village Apparatus, Bulawa District, Bone Bolango Regency.